(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Nepal is a small, lower-middle-income country; with a population of around 30 million. As per WHO, Nepal has a low doctor-patient ratio (0.7/1000) and even lower specialists (e.g., surgical) workforce (0.003/1000); additionally, data from Nepal Medical Council show the number of postgraduate specialists is 1/3rd of the total registered doctors. The mismatch in the doctor-patient ratio is further aggravated by the overwhelming number of doctors in urban areas; when 80% of the population are in rural Nepal. This inequitable discrepancy in the healthcare system requires: proper training of competent medical graduates, a fair distribution across the country, and effective changes in the healthcare system. Competency-based medical education plays an important role in: standardizing education, training competent doctors, and deploying them where they are needed the most. The Government of Nepal has recently established Medical Education Commission-which plans to oversee the entrance exams; and expand the postgraduate training to be conducted by private hospitals, previously not affiliated with any medical colleges or universities. Historically, Civil Medical School started training compounders and dressers in Nepal in 1934. A big milestone was achieved with the establishment of the Institute of Medicine under Tribhuvan University in 1972, which has continued to train all categories of health manpower needed in the country. In 2006 Nepal Medical Council developed “Regulations for Post-graduate Medical education”. Thereafter, several institutions started providing postgraduate training, for example: the BP Koirala Institute of Health Sciences, Kathmandu University, National Academy of Medical Sciences, and Patan Academy of Health Sciences (PAHS). The PAHS conducts PG programs and post-PG fellowships in line with competency-based medical education. In addition to formative assessments, research thesis, and a publishable article; PAHS requires its trainees to be certified in a pre-set of entrustable professional activities (EPAs) and to master eight Core Competencies domains in: Professionalism, Patient-centered care, Procedural skills, Clinical Reasoning, Communication, Scholarship, Leadership, Community orientation. The number of medical colleges in Nepal has since expanded to 24 (medical 21 and dental colleges 3). Private medical colleges make up about 3/4th of the total medical colleges in Nepal. This makes the inclusion and regulation of more components of the competency-based curriculum in postgraduate training programs, and its monitoring, somewhat of a challenge.